PEMANFAATAN MEDIA KOMUNIKASI DIGITAL DAN PENGARUHNYA TERHADAP KEUNGGULAN BERSAING BISNIS KULINER DI KOTA SERANG - Fajarwati, Noerma Kurnia; Susilawati, Eka; Wiyanto, Dana Rifqi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Meatballs are one of the most popular types of culinary in Indonesia. This culinary is favored by various age groups, social status, types of work, and even economic status. This study aims to determine the effect of media utilization on marketing performance which is strengthened by competitive advantage as an intervening for meatball traders in Serang City. The research sample was determined by the judgment sampling technique, namely only the meatball traders in Serang District with a total of 39 respondents. Analysis of research data using the Structural Equation Modeling approach which is processed with the SmartPLS program. From the research conducted, it can be concluded that 1) the use of media has a positive and significant effect on marketing performance; 2) The use of media has a positive and significant impact on competitive advantage; and 3) Competitive advantage has a positive and significant effect on marketing performance